Trafficking experiences and psychological dysfunction among female trafficking survivors returning to Vietnam - PhuongThao D Le, MPH (Elsevier, 2014)
Background: Studies have shown high levels of depression and post-traumatic stress disorder in female trafficking survivors and that mental disorders might be associated with factors such as pretrafficking childhood abuse, trafficking trauma, and unmet needs at post-trafficking. No study has provided comparisons of trafficking experiences and subsequent psychological dysfunction between individuals trafficked for different types of exploitation. Methods: A cross-sectional convenience sample of trafficked women and girls returning to and receiving assistance through a post-trafficking project in Vietnam's northern border region were recruited for the study. Participants who provided informed consent were interviewed about demographic characteristics, trafficking experiences including trafficking trauma, and self-reported health. Psychological dysfunction was assessed by a score on the self-reporting questionnaire-20 items. Univariate and bivariate statistics were done to examine distributions of trafficking experience and psychological dysfunction between women trafficked into sex work, marriage, and domestic servitude. Multivariate regression analyses were done to determine predictive factors of psychological status in this sample of returning trafficking survivors. Findings: 80 of 92 participants who agreed to participate in the study had complete data for the dependent variable; of whom 23 reported being trafficked into sex work, 15 into marriages, 12 into domestic servitude, and 30 in other/missing category. In the sample, age at trafficking averaged at 21·0 years (SD 5·5, range 14-45), duration of trafficking averaged at 7·9 months (SD 12·2, range 0-58), and most (n=57) were rescued by the police. Participants reported an average of 5·5 trauma items (of 18, SD 3·9, range 0-14). Individuals in domestic servitude reported the most amount of trauma (mean 8·4, SD 2·7, range 4-12), followed by those in sex work (mean 6·1, SD 3·9, range 0-14), and then those in marriages (mean 4·8, SD 2·7, range 0-10). The sample averaged a self-reporting questionnaire-20 score of 7·2 (SD 3·8, range 0-20). Regression analysis showed that individuals trafficked into marriages and domestic servitude reported significantly more psychological dysfunction than those trafficked into sex work, when adjusted for age, marital status, trafficking duration, and trafficking trauma (marriage: b=3·02, SE 1·17, p=0·012; domestic servitude: b=2·47, SE 1·21, p=0·045). Interpretation: Trafficking trauma and post-trafficking psychological dysfunction might be different between women trafficked into sex work, marriages, or domestic servitude. Provision of services for trafficking survivors should assess the types and severity of trauma and mental health status while remaining cognisant of the specific type of exploitation. Further evidence is needed to determine if these patterns are present in other samples of trafficking survivors. Funding: None.